Análise da implementação da logística reversa na indústria farmacêutica no Brasil - Barbosa, Felipe de Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The growth of the pharmaceutical industry in Brazil has brought a high rate of drug consumption and consequently a huge production of solid waste. Therefore, this paper intends to understand how reverse logistics of expired or disused drugs is carried out in Brazil. Decrees, resolutions, and laws were analyzed – mainly Law N°12.305/2010, the Law of the National Policy on Solid Waste – to understand who is responsible by its resolutions and the role of each one in the medicine reverse logistics chain. It was identified that Brazil has laws that encompass the entire production chain of medicines and that, if adhered, solve the problem of improper disposal of medicines. The country has about 3 thousand collection points and intends to reach up to 12 thousand points by September 2026. The increase in the number of collection points, attached with the dissemination of reverse logistics systems and the active participation of the population in these programs are the solutions to reduce the damage generated by the improper disposal of those products. Consequently, as a result of this paper, there is a path that aims at a more effective reverse logistics system. It was possible to conclude that few medicines are properly disposed of, compared to the amount of medicines consumed. Thus, this paper proposes a reverse logistics flowchart with the insertion of cashback as a way to increase the amount of waste disposed of properly. Using cashback systems will make sure that industries will use less raw material in its production, making its products costs less. With more waste disposed of properly, there will be also more effective recycling. This paper, therefore, contributes to those who seek to understand the main factors that affect the reverse logistics of medicines in Brazil and what can also be studied as improvement practices.

O crescimento da indústria farmacêutica no Brasil, trouxe consigo um alto índice de consumo de medicamentos e consequentemente uma enorme produção de resíduos. Dito isto, este trabalho busca compreender como a logística reversa de medicamentos vencidos ou em desuso é implementada no Brasil. Foram analisados decretos, resoluções e leis – principalmente a Lei N°12.305/2010, a Lei da Política Nacional de Resíduos Sólidos – para entender quem são os responsáveis e o papel de cada um na cadeia de logística reversa de medicamentos. Identificou-se que o Brasil possui legislações que englobam toda a cadeia produtiva de medicamentos e que, se levadas à risca, resolvem o problema do descarte inadequado de medicamentos. O país possuí cerca de 3 mil pontos de coleta e pretende chegar em até 12 mil pontos até setembro de 2026. O aumento no número de pontos de coleta, atrelado com a divulgação dos sistemas de logística reversa e participação ativa da população nestes programas são as soluções para reduzir os danos gerados pelo descarte inadequado destes produtos. Logo, como resultado desse trabalho, tem-se um caminho que visa um sistema de logística reversa mais efetivo. Foi possível concluir que poucos medicamentos são descartados adequadamente, comparando com a quantidade de medicamentos consumidos. Sendo assim, o trabalho propõe um fluxograma de logística reversa com a inserção do cashback como uma maneira de aumentar a quantidade de resíduos descartados adequadamente. A instituição do cashback assegura a recuperação de parte da matéria prima utilizada no ciclo produtivo bem como a redução de custo dos produtos. Com mais resíduos descartados adequadamente, haverá também uma reciclagem mais efetiva. O trabalho, portanto, traz uma contribuição para quem busca compreender os principais fatores que afetam a logística reversa de medicamentos no Brasil e o que também pode ser estudado como práticas de melhoria.
Analysis of the implementation of reverse logistics in the pharmaceutical industry in Brazil
Keywords: Reverse logistics; Pharmaceutical industry; Solid waste; Expired medicines; Logística reversa; Indústria farmacêutica; Resíduos sólidos; Medicamentos vencidos; Medicamentos em desuso